Characterization of the complete chloroplast genome of Arisaema erubescens (Wall.) Schott, a traditional Chinese medicinal herb. Issue 3 (2nd July 2020) - Zhang, Yan; Guo, Xiuzhi; Yan, Binbin
Abstract: Arisaema erubescens is a well-known medicinal plant in China. In this study, we sequenced the complete chloroplast (cp) genome sequence of A. erubescens to investigate its phylogenetic relationship in the family Araceae. The cp genome was 167, 607 bp in length, consisting of a pair of inverted repeats (IRa and IRb: 26, 193 bp) separated by a large single-copy region (LSC: 93, 660 bp) and a small single-copy region (SSC: 21, 561 bp). The GC content of whole cp genome is 35.3%. De novo assembly and annotation showed the presence of 114 unique genes with 80 protein-coding genes, 30 tRNA genes, and four rRNA genes. Phylogenetic analysis indicated that A. erubesc ens was closely related to A. franchetianum, and the genus Arisaema was sister to the genus Pinellia .